2020
DOI: 10.3390/genes11040353
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide Identification, Classification, and Expression Profiling Reveals R2R3-MYB Transcription Factors Related to Monoterpenoid Biosynthesis in Osmanthus fragrans

Abstract: Osmanthus fragrans is widely grown for the purpose of urban greening and the pleasant aroma emitted from its flowers. The floral scent is determined by several monoterpenoid volatiles, such as linalool and its oxides, which are a few of the most common volatiles and the main components of the essential oils in most sweet osmanthus cultivars. In addition, the relative contents of cis- and trans-linalool oxide (furan) may affect the aromas and quality of the essential oils. MYB proteins represent the largest fam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 50 publications
(65 reference statements)
0
14
0
Order By: Relevance
“…TFs from the R2-R3 MYB, WRKY, basic helix–loop–helix (bHLH) and ethylene-responsive factor (ERF) classes were differentially expressed in RU compared with GD. Of particular interest were MYB TFs as some MYBs have been linked to the regulation of both cuticle 41 and terpene biosynthesis 42 , 43 and, in apple, triterpenes are an integral part of cutin-associated and suberin-associated waxes 28 . A regularised canonical correlation analysis (rCCA) was performed to identify MYBs that were related to the production of specific types of triterpenes.…”
Section: Resultsmentioning
confidence: 99%
“…TFs from the R2-R3 MYB, WRKY, basic helix–loop–helix (bHLH) and ethylene-responsive factor (ERF) classes were differentially expressed in RU compared with GD. Of particular interest were MYB TFs as some MYBs have been linked to the regulation of both cuticle 41 and terpene biosynthesis 42 , 43 and, in apple, triterpenes are an integral part of cutin-associated and suberin-associated waxes 28 . A regularised canonical correlation analysis (rCCA) was performed to identify MYBs that were related to the production of specific types of triterpenes.…”
Section: Resultsmentioning
confidence: 99%
“…However, the nomenclature after R2R3-MYB is inconsistent, e.g. ~7% of studies refer to groups [ 62 , 63 ], ~31% refer to subfamilies [ 10 , 64 ], and ~54% refer to subgroups [ 23 , 65 ], with clade or cluster used occasionally [ 66 , 67 ]. Subfamilies and subgroups are the most common subsequent appellations after family.…”
Section: Genome-wide Characteristics and Evolution Of The R2r3-myb Ge...mentioning
confidence: 99%
“…The number of OfMYB-related genes was more significant than that observed in other plants reported over the recent years ( Table 1 ; Jin et al, 2017 ), such as 109 genes in peach ( Zhang et al, 2018 ). In our study, we identified 212 MYB-related genes in O. fragrans , a value close to the number of R2R3-MYB genes in O. fragrans (243 genes) ( Li et al, 2020a ), thus representing the largest subfamily of MYB genes, which play critical roles in various processes of growth, development, and responses to abiotic or biotic stress. While high, the number of R2R3-MYB subfamily members did not exceed the number of 1R-MYB subfamily members.…”
Section: Discussionmentioning
confidence: 57%
“…Because of its pleasing floral fragrance and multitudinous flowers, sweet osmanthus is widely cultivated in China as a common landscape tree species ( Huang et al, 2015 ). Sweet osmanthus is relevant to several industries, including tea, food, and perfume production ( Li et al, 2020a ). The floral fragrance of sweet osmanthus has been comprehensively studied in terms of compound identification and classification.…”
Section: Introductionmentioning
confidence: 99%